Western corn rootworm: ecology and management - Vidal, S.; Edwards, C. R.; Edwards, C. R.; Kuhlmann, U.; Kuhlmann, U.; Vidal, S. (Wallingford :CAB International, 2005)
This book provides a comprehensive review of the current knowledge of Western corn rootworm, Diabrotica virgifera virgifera, and how it might be managed both in North America and in Europe. Comparisons are drawn between plant protection techniques currently applied in North America and their potential application in Europe. Cultural, biotechnical and biological control measures are also addressed, as are ecological baseline data, i.e. population dynamics of the pest in North America and Europe, economic thresholds and aspects of its behaviour.
Keywords: EE110 - Agricultural Economics; FF620 - Plant Pests, (New March 2000); HH100 - Biological Control; HH200 - Environmental Pest Management; ZZ332 - Animal Ecology; ZZ900 - Techniques and Methodology; Europe; North America